حجية الدفاتر التجارية المحاسبية الإلكترونية في الإثبات وفق القانون 07-11 المتعلق بالنظام المحاسبي المالي - حسين, بوزيزة; إيمان, عبد اللاوي (جامعة الوادي - University eloued, 2022)
يعد التطور التكنولوجي أحد أهم المحطات ذات التأثير المباشر على كافة الجوانب في حياة الإنسان، وباعتبار النشاط التجاري ركيزة أساسية للتقدم والازدهار، فإن ذلك جعله يحاول دائما مواكبة كافة التطورات الحاصلة، حتى يضمن سيطرة كاملة على كل جزئيات العمل التجاري، وبالتالي تحقيق أهم مبادئه كالسرعة والائتمان، وقد كان لإدخال الرقمنة في مسك الدفاتر التجارية المحاسبية التي من خلالها يمكن ضبط محاسبة مالية دقيقة، أن تسمح بمعالجة كل الاختلالات الحاصلة في المجال الضريبي واعتمادها إحدى الوسائل المتطورة في الاثبات، لما للتكنولوجيا من تأثيرات إيجابية يمكن الاستعانة بها من طرف الجهات القضائية ومصالح الضرائب في كل ما يتعلق بالإثبات Technological development is one of the most important stations with a direct Technological development is one of the most important stations with a direct impact on all aspects of human life, and as a key pillar of progress and prosperity, this has always made him try to keep up with all developments, in order to ensure full control over all aspects of the business, thereby achieving its most important principles such as speed and credit, and the introduction of digitization in accounting business bookkeeping through which accurate financial accounting can be adjusted, allowing all imbalances in the tax field to be addressed and adopted as one of the means of digitization in accounting business books through which accurate financial accounting can be adjusted, allowing all imbalances in the tax field to be addressed and adopted as one of the means of Advanced evidence, because of the positive effects of technology that can be used by the judiciary and tax interests in all matters of proof
مذكرة ماستر
Keywords: الدفاتر التجارية الالكترونية، المحاسبة المالية، السرعة والائتمان; Electronic business books, financial accounting, speed and credit